Indigoid Photoswitches: Visible Light Responsive Molecular Tools - Petermayer, Christian; Dube, Henry (Accounts of Chemical Research, 2018)
ConspectusIndigoid photoswitches comprise a class of chromophores that are derived from the parent and well-known indigo dye. Different from most photoswitches their core structures absorb in the visible region of the spectrum in both isomeric states even without substitutions, which makes them especially interesting for applications not tolerant of high-energy UV light. Also different from most current photoswitching systems, they provide highly rigid structures that undergo large yet precisely controllable geometry changes upon photoisomerization. The favorable combination of pronounced photochromism, fast and efficient photoreactions, and high thermal bistability have led to a strongly increased interest in indigoid photoswitches over the last years. As a result, intriguing applications of these chromophores as reversible triggering units in supramolecular and biological chemistry, the field of molecular machines, or smart molecules have been put forward. In this Account current developments in the synthesis, mechanistic understanding of light responsiveness, advantageous properties as phototools, and new applications of indigoid photoswitches are summarized with the focus on hemithioindigo, hemiindigo, and indigo as key examples.Many methods for the synthesis of hemithioindigos are known, but derivatives with a fourth substituent at the double bond could not easily be prepared because of the resulting increased steric hindrance in the products. Recent efforts in our laboratory have provided two different methods to prepare these highly promising photoswitches in very efficient ways. One method is especially designed for the introduction of sterically hindered ketones while the second one allows rapid structural diversification in only three high-yielding synthetic steps.Given the lesser prominence of indigoid photoswitches, mechanistic understanding of their excited state behavior and therefore rational design opportunities for photophysical properties are also much less developed compared to, for example, azobenzenes or stilbenes. By testing different substitution patterns, we were able to produce strongly beneficial property combinations in hemithioindigo, hemiindigo, or indigo photoswitches, for example, red-light responsiveness together with very high thermal bistability of the switching states. This is of particular importance for photopharmacological and biological applications of these switches to reduce the damage from high-energy light and to enable deep penetration of the light into tissues. An additional ground state twisting in hemithioindigo allowed us to control the type of light-induced bond rotation simply by the polarity of the solvent. With the aid of time-resolved spectroscopy and quantum yield measurements, we could show that in apolar cyclohexane exclusive double bond rotation takes place while in polar DMSO sole single bond rotation is observed. Such precise control over geometrical changes is of great interest for the construction of future sophisticated molecular machinery. In this field, we have introduced hemithioindigo photoswitches as novel core structure for molecular motors providing very fast directional motions upon irradiation with visible light. The mechanism of the directional rotation adheres to a four-step process, which could directly be observed in situ with a slower second-generation motor. Further applications of indigoid photoswitches were made in our laboratory in the realms of photocontrolled folding and host-guest chemistry as well as in molecular digital information processing showcasing the great versatility and enormous future promise of indigoid photoswitches.
CRIS-Team Scopus Importer:2020-04-02